ANALISIS SIKAP ILMIAH SISWA PADA MATERI EKOSISTEM DI SMA NEGERI 2 KOTAPINANG - Hasmi Syahputra Harahap; Harahap, Ilham Hakiki (Pendidikan Biologi Universitas PGRI Ronggolawe Tuban, 2022)
The causes of the low literasi science in indonesia can be seen based on gender, economic and social, as well as immigration. Related to gender, in a learning process in class teacher does not distinguish between gender students, but in this case very students need to understand scientific attitude based on gender. This research aims to determine the scientific attitude of tenth graders of SMA Negeri 2 Kotapinang and students' scientific attitudes towards male and female students. The research sample consisted of 107 tenth grade students from a population of 107 students consisting of three classes at SMA Negeri 2 Kotapinang. The technique of taken sample using the techniques of total sampling in order to better data analysis. This research using descriptive method with quantitative approach. The research instrument was in the form of a non-test, namely a questionnaire on students' scientific attitudes with using likert scale. Data analysis techniques to do with descriptive statistics acording to average and inferential. The results of the study show that the scientific attitude of tenth graders at SMA Negeri 2 Kotapinang is quite good (73,63), the scientific attitude of students for male students was obtained at (70.62) and female students were obtained at (75.15) which were both classified as good.